Comparison of DNA extraction methods from dentine (of tooth) as a source of genetic material - Ahmad, Azlina (Pusat Pengajian Sains Pergigian, Universiti Sains Malaysia, 2011)
Mitochondrial DNA (mtDNA) is a maternally inherited hereditary material locatt-d in mitochondria. Previous studies on mtDNA proved that the mutations are closely related with a number of genetic illnesses and exploitable for forensic identification. Those findings imply the importance of mtDNA in the scientific field. The mtDNA can be found in abundance in tooth dentin where it is being kept protected by the enamel, the hardest outer part of the tooth. In this study, two techniques of mtDNA extraction were compared to determine the efficacy between the two techniques. After the extraction of tooth, the tooth was kept at -20°C until use. Later, pulp tissue and enamel were excised out using dental bur and only the root dentin was utilized for the isolation of mtDNA by crushing it mechanically into powder form. The mtDNA was then extracted using the two published methods, Pfeiffer and Budowle and then subjected to spectrophotometry for DNA quantification and purity, Polymerase chain reaction (PCR) amplification of hypervariable-two region of mtDNA, followed by DNA sequencing to analyze the reliability of the extraction techniques. In conclusion, both techniques proved to be efficient and consistent for the extraction of mtDNA from tooth dentin.